ADRC controller for buck converter - inverter system for photovoltaic applications - Esteva Pérez, R (International Journal of Intelligent Systems and Applications in Engineering, 2025)
This paper presents the design and simulation of the Active Disturbance Rejection Control (ADRC) for a buck-boost converter-inverter system powered by photovoltaic panels. The system features a two-stage configuration, based on a buck-type DC/DC converter and a single-phase inverter, connected in cascade. The objectives of this work are the voltage regulation at the output of the buck converter and the sinusoidal current tracking at the output of the inverter. Active Disturbance Rejection Control is employed from the perspective of differential flatness and Generalized Proportional Integral (GPI) extended state observers. The simulations of the proposed photovoltaic system are carried out in the MATLAB/Simulink environment. Additionally, to evaluate the performance of the photovoltaic system and the robustness of the controller, simulation results are presented under input voltage variations and load disturbances. Furthermore, Total Harmonic Distortion (THD) graphs of the sinusoidal current at the output of the inverter are provided. The simulation results demonstrate appropriate behavior of the Active Disturbance Rejection Control, as evidenced by a short settling time of the buck converter and accurate current reference tracking.